Screening of non-edible (second-generation) feedstocks for the production of sustainable aviation fuel - Mofijur M.; Ahmed S.F.; Rony Z.I.; Khoo K.S.; Chowdhury A.A.; Kalam M.A.; Le V.G.; Badruddin I.A.; Khan T.M.Y. (Elsevier Ltd, 2024)
This paper examines the potential of suitable second-generation feedstocks for sustainable aviation fuel production, theoretically based on fatty acid-based fuel properties. The fatty acid composition of 38 s-generation feedstocks was collected from the literature. The fuel properties of these feedstocks were then calculated using empirical formula and assessed according to international fuel standards including American and European standards. The selected feedstocks were assessed and ranked using a multi-criteria decision analysis (MCDA) tool, i.e., PROMETHEE GAIA, to identify the suitability of the sources based on kinematic viscosity (KV), density (D), higher heating value (HHV), cetane number (CN), iodine value (IV), oxidation stability (OS), and cold filter plugging point (CFPP). It was found that 20 of the 38 feedstocks meet international fuel standards. The utilisation of the MCDA tool indicates that Ricinus communis is the highest-ranked feedstock for sustainable aviation fuel production, followed by the Azadirachta indica feedstock, with Sterculia feotida L. the lowest-ranked feedstock. The assessment of the properties of ranked feedstock against aviation fuel standards, including Jet A and Jet A1, reveals that the kinematic viscosity of all the feedstocks meets both these standards. However, fatty acid-based fuel properties could not satisfy the international aviation fuel standards for D, HHV, and freezing points. Further experimental work is recommended, including improvements in the processing and modification of biofuel produced from second-generation feedstocks. It is recommended that a comprehensive action plan is required to facilitate the introduction of sustainable biofuel from non-edible sources for the aviation industry, such as the adjustment of the current jet fuel standards. 2022 Elsevier Ltd